2004
DOI: 10.1016/j.jfluidstructs.2004.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of flow-induced noise in a two-dimensional centrifugal pump. Part I. Hydrodynamics

Abstract: This paper is concerned with the simulation of the flow in a flat, 'two-dimensional' laboratory centrifugal pump. The main concern of the study is the calculation of the flow-induced noise. The aim of the present paper is to develop a computationally simple and fast method which is capable of giving a useful estimate of the noise-generating 'background-flow'. A companion paper describes the hydroacoustic part of the analysis. In the numerical flow model of the pump, the inlet is modelled by a point source and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 28 publications
(30 reference statements)
0
40
0
Order By: Relevance
“…Many studies have shown that vibration signals caused by hydraulic factors mainly concentrate in low frequency band [22][23][24]. So vibration signals in low frequency band of two model pumps were investigated to analyze influence of slope volute on vibration characteristic in centrifugal pump.…”
Section: Vibration Characteristics Comparision Of Two Pumpsmentioning
confidence: 99%
“…Many studies have shown that vibration signals caused by hydraulic factors mainly concentrate in low frequency band [22][23][24]. So vibration signals in low frequency band of two model pumps were investigated to analyze influence of slope volute on vibration characteristic in centrifugal pump.…”
Section: Vibration Characteristics Comparision Of Two Pumpsmentioning
confidence: 99%
“…The findings show that rounding out the blade inlet can improve the cavitation performance 2 of the inducer. The rotation cavitation of one channel and four channels of the inducer is simulated by adopting the unsteady cavitation model (Langthjem & Olhoff, 2004). The complex cavitation flow of the inducer is solved using the CRUNCH program and multiple unstructured grids (Li, 2004).…”
Section: Research Statusmentioning
confidence: 99%
“…A hybrid method combining CFD with Lighthill acoustic analogy has been widely used to elucidate and predict acoustic generation [17][18][19]. Langthjem et al [20,21] applied it for noise calculation in a two-dimensional centrifugal pump and concluded that the main noise source was the dipole source. The dipole source was defined as an unsteady fluid force acting on the wall surface, including the impeller dipole source and the volute dipole source in centrifugal pumps.…”
Section: Introductionmentioning
confidence: 99%